Predicting performance of elite kickboxers using the multi-states theory framework - Morrone, M.; Ventura, L.; Roggio, I.; Di Blasio, A.; Ruiz, M.; Deriu, F.; Cugusi, L.; Manca, A.; Robazza, C. (European Journal of Sport Science, 2024)
Using the multi-states (MuSt) theory framework, this study examined the interplay between self-confidence, emotional arousal control, worry, concentration disruption, challenge and threat appraisals, psychobiosocial experiences, and self-evaluated performance of medalist kickboxers involved in the WAKO World Kickboxing Championship 2021. Participants were 103 gold, silver, or bronze medalists (58 women and 45 men), aged 18-39 (M = 25.16 ± 4.54 years), who were contacted via email and social media and asked to fill an online survey 3 months after the event. According to the MuSt theory predictions, self-confidence and emotional arousal control were positively related to challenge appraisal, functional psychobiosocial experiences, and self-evaluated performance. Worry and concentration disruption were positively associated with threat appraisal, and negatively related to functional psychobiosocial experiences; concentration disruption was also negatively related to self-evaluated performance. Results from path analysis revealed a positive indirect link from self-confidence to self-evaluated performance via challenge appraisal and psychobiosocial experiences. Negative indirect links from worry and concentration disruption to self-evaluated performance through threat appraisal and psychobiosocial experiences were significant. A positive indirect effect from emotional arousal control to self-evaluated performance via psychobiosocial experiences was also shown. The findings are discussed in light of the MuSt theory.